Dreaming and Neuroesthetics - Barcaro, Umberto; Paoli, Marco (Frontiers in Human Neuroscience, 2015)
This paper, which is limited to the art of painting, aims to support the idea that a substantial insertion of concepts and methods drawn on dream psychology and dream neuroscience can contribute to the advancements of Neuroaesthetics. The historical and scientific reasons are discussed that have determined the so far poor role played by the dream phenomenon in the developments of Neuroaesthetics. In the light of recent advancements in psychophysiological research, a method of analyzing artistic products is proposed that is based on the recognition of precise features proper of the dreaming experience. Four examples are given of application of this method, respectively regarding works by Giorgione, Leonardo da Vinci, Vermeer, and Millais.